Tourism Experience Design dan Penciptaan Nilai Pelanggan Pada Pariwisata di Bali - I Gusti Ketut Adi Winata; Ni Luh Putu Eka Yudi Prastiwi; Ni Made Wulan Sari Sanjaya (ARTHA SATYA DHARMA, 2018)
Tourism industry is the most important economic activities in Bali. Generally high and low levels of economy in Bali is reflected in the tourism industry. Tourism industry in Bali are required to improve in order to create value added for customers. The increase of domestic and foreign tourists is not followed by the increase of the hotel occupancy rate in Bali. Not only giving satisfaction to customers through a visual experience but also an emotional experience should be a concern. Tourist experience can be a positive experience if their expectations when visiting are fulfilled, viceversa the tourist experience can be negative if the tourist expectations when visiting are not fulfilled. The aim of this paper is to describe a role off tourism experience design to create customer value, especially in Bali. The diverse of Balinese culture can be an opportunity to create variety of a product. The method used is qualitative descriptive with literature approach. This research describe a role model of product development experience by combining the concepts of design and culture to create value added for consumers. The products produced by considering aspects of the experience that is created and cultural variations in each area in Bali. The existence of the variety of products and a touch of different cultures can create variations of value added for customers.